Analysis of Factors that Influence the Occuration of Early Rapture of Money in Particular Patients in Pragaan Public Health Center, Sumenep Regency - Aziz, Abdul; Farida, Siti; Suhita, Byba Melda (Journal for Quality in Public Health, 2021)
Pregnancy is a moment that is highly desired by husband and wife. This can make the family more harmonious because it has a child who is always coveted. But in reality, sometimes pregnancy is accompanied by several obstacles, such as premature rupture of membranes. The purpose of this study is to analyzethe effect of economic status, fetal position and family support on the incidence of premature rupture of membranes in inpartu patients at the Pragaan Health Center, Sumenep Regency. The design of this research is an observational quantitative research with a cross sectional approach with the focus of the research being directed at analyzingthe effect of economic status, fetal position and family support on the incidence of premature rupture of membranes in inpartu patients at the Pragaan Health Center, Sumenep Regency. The total population of 160 respondents and a sample of 100 respondents were taken by Accidental Sampling technique. The findings show that almost half of the respondents haveeconomic status middle class category as many as 42 respondents (42%).Almost half of the respondents experienced an anterior fetal position as many as 39 respondents (39%). Most of the respondents have family support in the less category as many as 62 respondents (62%). Most of the respondents experienced premature rupture of membranes as many as 56 respondents (56%). Based on the results of the Logistics Regression analysis shows that the p-value <0.05 then H1 is accepted so it is concluded that there is an effect of economic status, fetal position and family support for the incidence of premature rupture of membranes in inpartu patients at the Pragaan Health Center, Sumenep Regency. It is hoped that both pregnant women can manage the needs and things that must be done during pregnancy until delivery, starting from maintaining a lifestyle and even monitoring the development of the fetus in order to reduce the incidence of KTD.